Сумське товариство «Меморіал» та пам’ять про політичні репресії - Рожкова, Л.І. (Сіверщина в історії України, 2021)
У статті висвітлюється створення та діяльність Сумського
історико-просвітницького товариства «Меморіал». Проаналізовано обставини протистояння «Меморіалу» з органами компартійно-державної влади наприкінці 1980-х – на початку 1990-х рр.
Розкрито програмні та організаційні засади діяльності товариства. Основну увагу авторка приділяє пошуково-дослідницькій роботі організації, спрямованій на збереження історичної пам’яті
про політичні репресії комуністичного режиму у 1930-х – на початку 1950-х рр. Зроблено спробу охарактеризувати особистості репресованих сумчан крізь призму усних свідчень та автобіографічних творів учасників товариства «Меморіал». На основі
спогадів репресованих реконструйовано окремі аспекти повсякдення політичних в’язнів у системі ГУЛАГу. Зазначено вклад товариства «Меморіал» у підготовку обласного тому науково-документального видання «Реабілітовані історією. Сумська область». The article covers the creation and activities of the Sumy historical and
educational society «Memorial». The founders of the Society in Sumy were
representatives of the creative intelligentsia and teachers. The circumstances of
Memorial’s confrontation with the party and state authorities in the late 1980s
and early 1990s are analyzed. The program and organizational principles of
the society’s activity are revealed. During 1990 – to beginning 2000 activity of
organization came true after searching and historical-elucidative directions.
Active voice in-process Sumy society «Memorial» was taken by former political
prisoners Boris Bliner, Mariia Yarova, Dmytro Moiseienko, married couples
of Pashchyshynsky, members of families of subjected to repression Emma
Novobrantseva, Ihor Yelfimov, Alla Kryhanova. Creation of collection of documents,
that includes information about subjected to repression, remembrances,
documentary photographs, became a selfless job of Sumy society performance.
On the basis of collected by society «Memorial» of data is certain basic directions
of repressions at the end of 1930 th – 1940-х.
An attempt to describe personalities of subjected to repression Sumy through
the prism of verbal certificates and autobiographic works of participants of society
«Memorial» is done. Considerable attention is spared to autobiographic works of
Sumy Boris Bliner, that characterize the atmosphere of daily occurrence of political
prisoners of HULAHu, contain mentions about bright personalities of slaves of
Kolyma. The fates of subjected to repression are traced after serving of punishment,
and also the facts of their rehabilitation are fixed. The deposit of society is marked
«Memorial» in preparation regional to the volume scientifically - documentary
edition «Rehabilitated by history. Sumy area».
On the basis of the conducted analysis of activity of Sumy historical-educational
society «Memorial» is done conclusion about the ponderable contribution of
organization to proceeding in rights subjected to repression by the communist mode
and maintenance of historical memory about political repressions.